Dodecyl methacrylate as a crosslinker in the preparation of tough polyacrylamide hydrogels - ABDURRAHMANOĞLU, SUZAN (ELSEVIER SCI LTD, 2011)
Copolymerization of acrylamide with dodecyl methacrylate (C12) solubilized in aqueous micelles of sodium dodecyl sulfate produces tough hydrogels exhibiting moduli of elasticity around 1 kPa. Swelling and gel fraction measurements show that the hydrophobic associations acting as temporary crosslinks are too strong to be destroyed in water during the expansion of the gel network. An order of magnitude larger value of loss factor tan delta of the hydrogels formed using the hydrophobe C12 as compared to the conventional hydrogels indicates the dynamic nature of their crosslink zones. The hydrogels are more homogeneous than the corresponding gels prepared by a chemical crosslinker, as determined by the static light scattering measurements. Mechanical tests indicate that, in addition to the dodecyl domains, permanent crosslinks are also needed to obtain hydrogels that are mechanically stable up to 250% elongation ratios. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Hydrogels; Toughness; Elasticity; SPATIAL INHOMOGENEITY; NETWORK STRUCTURE; TOPOLOGICAL GEL; STRENGTH; FRACTURE